Effect of myricetin on the transgenic Drosophila model of Parkinsonâs disease - Gulshan Ara; Mohammad Afzal; Smita Jyoti; Yasir Hasan Siddique (Faculty of Pharmacy, Cairo University, 2017)
Parkinsonâs disease (PD) is a progressive neurodegenerative disorder that affects movement, balance and fine motor control mostly in the elderly population. It is characterized by the progressive loss of neurons in substantia nigra resulting in the depletion of dopamine. Due to ethical reasons the study cannot be performed directly on humans, hence various genetic models of PD based on alpha synuclein, primarily the transgenic over expression of mutant or wild forms in mice or flies are available. In the present the study, we decided to study the effect of myricetin on the climbing ability and life span of PD flies expressing human alpha synuclein in the brain. The PD flies were exposed to 10, 20 and 40Â ÂµM of myricetin for 24Â days and then assayed for climbing ability. For survival assay the PD flies were transferred to a new diet at 3Â day interval having the desired concentration of the myricetin until the last one will die. The PD flies exposed to various doses of myricetin showed not only a dose dependent significant delay in the loss of climbing ability but also increased life span of flies. The results suggest that myricetin is potent in delaying the loss of climbing ability and increases the life span of PD flies expressing human alpha synuclein in the brain. Keywords: Myricetin, Drosophila, Parkinsonâs disease, Climbing ability, Life span